Zonation of firefly species and their display trees along kerteh river, Terengganu - Wan Faridah Akmal Wan Jusoh; Choong-Hay Wong; Nor Rasidah Hashim (Pusat Sistematik Serangga ,UKM, 2011)
The zonation of firefly species and their display trees under Kerteh River, Terengganu was studied in July 2009. Results showed that the adults of two firly species, ( Pteroptyx tener and pteroptyx bearni) were congregating on 170 trees (belonging to 27 different species), located along 1-15 km from the river mounth. it was observed that the spatial distributions of the two pteroptyx species were divided into three zones along the river. The mangrove habitats in the study area were in relatively good condition as evidenced from the high number of plant species, and that such condition was important for the coexistence of the two pteroptyx spp